Environmental assessment in tropical streams by using abundance-biomass curves and W index in fish assemblages - Mise, Fábio T.; Message, Hugo J.; Pagotto, João P. A.; Goulart, Erivelto (Fundação Zoobotânica do Rio Grande do Sul, 2018)
We investigated the fish fauna response to different environmental conditions of urban (three) and rural (seven) streams through biomass/abundance curves and W index of environmental stress. Negative values of W indicate some level of stress, while positive values suggest environments with lower stress. Dissolved oxygen, marginal erosion (both left and right margins), mesohabitat diversity, and percentage of canopy cover were measured to characterize the 10 streams analysed around Maringá city, Southern Brazil. Fish were sampled by electrofishing, then identified and weighed. Results showed negative values of W to the urban streams and positive to the rural. Urban streams showed a tendency to have assemblages of fish with lower biomass and greater abundance (r-strategists).

A resposta da fauna de peixes a diferentes condições ambientais foi verificada em riachos urbanos (três) e rurais (sete), por meio de curvas de abundância/biomassa e o índice W de estresse ambiental. Valores negativos de W indicam níveis consideráveis de estresse, enquanto valores positivos sugerem ambientes com menos estresse. Para caracterizar os 10 riachos no sudeste do Brasil foram medidos oxigênio dissolvido, erosão das margens (direita e esquerda), diversidade de mesohabitats, e porcentagem de dossel. Os peixes foram amostrados por meio de pesca elétrica, identificados e pesados. Os resultados mostraram valores negativos de W para os riachos urbanos e positivos para os rurais. Os riachos urbanos mostraram uma tendência a ter assembléias de peixes com menor biomassa e maior abundância (r-estrategistas).
Avaliação ambiental em riachos tropicais utilizando curvas de biomassa-abundância e índice W em assembleias de peixes
Keywords: Neotropical region; biotic indices; stream ecology; biodiversity; Região Neotropical; índices bióticos; ecologia de riachos; biodiversidade